Umbrella-shaped wideband MIMO wireless communication antenna - Mohammed Naser, Hussein; Al-Ani, Oras Ahmed; Farhan Mosleh, Mahmood; Arith, Faiz (Middle Technical University, 2023)
A Circular Polarization (CP) Multiple Input Multiple Output (MIMO) system was used in this study with additional components for contemporary communication systems developed. There are 4 elements in the model. On the printed circuit board, each element has a dual-fed with two ports positioned at each of the four corners of smart devices (PCB). A Rogers RO3003 substrate with a dielectric structure size of (64.59 × 64.59) mm2. geometrical shape 50-Ohm microstrip lines are used to feed the antenna ports. To accomplish polarization and variety properties, microstrip feed lines are positioned orthogonally. According to the paradigm results, the operational frequency for each portwas 4.25 GHz, and the system's operating frequency was 4.23 GHz while diversity gains (DG) of the MIMO antennas were about 10, the gain was suitable (around 7 dB), and Less than 0.0001 was the envelope correlation coefficient (ECC). Additionally, the outcomes demonstrate that the MIMO system may operate in a sub-6 band that is ideal for smart device applications.